Comparison of the sevoflurane versus desflurane anaesthesia on the recovery of airway reflexes and cognitive function: An original research - Anish Nelson; S Sudhakar; Jagannath Mishra; Hemanth Kumar Tirupathi; Vishnu Gowtham Marella; Vishal S Kudagi (Journal of Pharmacy and Bioallied Sciences, 2023)
Background and Objectives: Sevoflurane and desflurane virtually equally dissolve in blood gases, yet current research suggests that desflurane helps in a quick return of airway reflex than sevoflurane however the return of cognitive activity fluctuates greatly. In order to compare the lengths of time required to recover after sevoflurane and desflurane anesthesia, the current research was conducted. Materials and Methods: Current study was randomized that included 100 subjects who were posted for cholecystectomy (elective). Only adult and non-obese subjects were included in the study. The intended anesthetic agents sevoflurane and desflurane were utilized in the study and all the protocols were followed for the surgery. After the end of the surgery, tests for regaining cognitive function and airway reflexes were carried out, and different time intervals were recorded. The values were recorded and compared for the variances while considering the P < 0.05 as significant. Results: The mean T1 was 8.19 ± 3.28 min for sevoflurane and was 5.82 ± 4.02 min. There was no significant variance between the two agents for the T1, 2 (P = 0.013 and 0.110 respectively). After the inhalation anesthetics ceased at T1, desflurane patients responded to verbal commands more quickly than sevoflurane patients (5.824.02 vs. 8.193.28 min). The SOMCT and swallowing test were similarly completed more quickly by desflurane-treated patients than by sevoflurane-treated patients (T3VST4) (13.693.37 vs. 10.024.86 min, P = 0.008 and (14.094.30 vs. 9.824.50 min, P 0.001, respectively). For the T3, 4-time intervals, there was a significant difference between the sevoflurane and desflurane groups. Conclusion: Desflurane causes patients to recover more quickly from laparoscopic cholecystectomy under controlled circumstances than sevoflurane does.